(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2025)
The aim of this study was to examine the relationship between bilateral asymmetry (BA) and bilateral deficit (BLD) with the horizontal force–velocity profile (HFVP) in non-athletic adolescents participating in a social sports workshop in the city of Chillán. A quantitative approach was employed using a non-experimental, descriptive, and correlational cross-sectional design. The study population consisted of 11 nonathletic adolescents enrolled in a community-based football workshop in Chillán. BA was assessed through the calculation of the asymmetry index (AI), while BLD was quantified using the Bilateral Index (%BI). The HFVP was evaluated through video recordings, with data analysis conducted using the MySprint application. As the data followed a normal distribution, Pearson’s correlation test was applied to examine the relationships between BLD and BA with HFVP. Statistical analyses were performed using JASP software version 0.19.1.0 for Windows. The correlations between BA and HFVP variables (F0, VO, P_máx, RF_10m, RF peak) were not statistically significant, nor were the correlations between BLD and HFVP parameters (p < 0.05). In conclusion, neither bilateral asymmetry nor bilateral deficit were correlated with horizontal force–velocity profile parameters in untrained adolescents.